Pemanfaatan Youtube sebagai Media Pembelajaran Menulis Puisi - Marlina Bakri; Yusni Yusni (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2021)
Nowadays technology and information are experiencing rapid development so that computer-based technology can be applied to obtain information, especially in education. The internet provides many applications for integrating technology in learning. In the current era, human interaction activities can use innovative information or communication networks. In the current era, human interaction activities can use innovative information or communication networks. One of the media that can be integrated into learning is the use of Youtube media. The purpose of this study was to describe the extent to which Youtube can be used as a learning medium for writing poetry. This research method is descriptive qualitative with the number of respondents as many as 40 students. The data collection was done through poetry writing test sheet. The findings of this study are that the Youtube teaching media used are in line with the interests of students, which are currently one of the main goals of the millennial generation to seek various educational content in the form of videos, to create creativity and quality in writing poetry. The results of this study also revealed that during the learning process using Youtube media, students were seen actively writing poetry which was quite creative and had a different writing style from each work produced. The findings of this study recommend using Youtube as a medium in the literature learning process.